Addressing issues affecting public restrooms in Singapore : a social and mechanical engineering initiative - Kwek, Amos Chin Hong (Nanyang Technological University, 2020)
This report highlights two solutions – a social engineering and a mechanical engineering initiative, to counter some of Singapore’s public restroom issues found through an initial public survey. The first solution, as described in Chapter 3, involves the engineering of a sensible standardization of the washing area, while the second solution, taking up the bulk of the report, proposes an innovative door configuration. Chapter 4 consists of the design methodologies used which ties to the design conceptualization phase, and this leads to a finalized design described in Chapter 5 which highlights essential components and their dimensions. The door configuration, taking into account the space necessary within a toilet cubicle, integrates existing components such as rollers and T-tracks to create a sliding door mechanism aimed at reducing the cubicle size without jeopardizing users’ comfort and allowing more flexibility in restroom design. Finally, Chapter 6 validates the results from a second survey on product design and concludes the report.